Análisis multitemporal de los cambios de uso de suelo, de las microcuencas productoras de agua, en los sistemas de riego públicos de la Cuenca Superior del Río Catamayo - Agurto Mendoza, Kathya Daniela (2024)
The continuous human intervention in the hydrographic basins has negative effects on their original vegetation, with changes in land use resulting in the loss of forest cover and a reduction in water resources, thereby affecting agricultural production. Multitemporal analysis is a tool that allows identifying these changes over time, helping to understand the evolution of the natural environment. This study focused on analyzing changes in land use between 2010 and 2022, and projecting these changes for 2030 and 2060. Using techniques such as photointerpretation and orthophoto digitization, along with geographic information systems, these changes were examined using tools like the Intersec module of ArcGIS and the change matrix, as well as the LCM model of TerrSet for future projections. The results indicate that, in the total area of 187.70 km2 in the studied microbasins, 92.31% remained unchanged in their coverage, while 16.98% experienced changes to other types of coverage, such as deforestation for the expansion of pastures and agricultural lands. The modeling shows a reduction of forest by 44.05% for 2030 and 42.24% for 2060, while pastures and agricultural lands show an increase of 17.56% and 19.15% respectively in the study area. It is observed that the Campana and Capamaco microbasins have a low degree of intervention, while Mazanamaca and Aguacolla show a medium degree, and San Agustín presents a high degree of intervention due to the increase in agricultural lands and the decrease in natural vegetation.